EUROPEAN UNION and AFRICAN, CARIBBEAN, and PACIFIC COUNTRIES ECONOMIC PARTNERSHIP AGREEMENTS and their IMPLICATIONS on the AGRILCTURAL TRADE of the SUDAN - Azhari Ibrahim dowina; Mohammed Ahmed Osman Ibnouf; Hag Hamed Abdel Aziz (IJRDO - Journal of Business Management, 2019)
The objective of this paper is to assess the potential implications of the Sudan signing of the Economic Partnership Agreement between the European Union and African, Caribbean, and Pacific Countries (EPA) on the Sudan agricultural trade relationships. More specifically it attempts to estimate effects of the EPA on production, demand, and trade of agricultural commodities of the Sudan domestically and abroad. A multimarket model with Armington specification is applied to achieve the paper objectives. The model is based on the average data of years 2014 and 2015 for the main agricultural exports of Sudan to the EU, namely gum Arabic, sesame, cotton and groundnuts. The model results revealed that, removal of tariffs on these agricultural commodities by the EU resulted in an increase of the export of cotton, sesame, groundnuts and gum Arabic by 92%, 150%, 154% and 110%, respectively and a decrease their exports to the rest of the world. This may be attributed to the increase of the EU consumers demand for these products in response to the reduction of their prices after application of zero tariffs. The net result for Sudan is the increase in aggregate output of agricultural production and improvement in foreign exchange earnings with slight negative impact on domestic demand. While it showed an improvement in the producer surplus, consumer surplus and net welfare in some case. The simulation results of the zero tariff show negative impacts on the domestic producer and consumer prices, this lead to reduction in domestic production, and increases the domestic demand.